The phenomenon of change in the context of the fate of A. A. Blok - Jing, Lu (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The author considers the experience of experiencing revolutionary changes by the poet A. A. Blok, one of the most sensitive and principled witnesses of them. Examples of the experience of broken ontological unity in the era of change by a specific subject are demonstrated. The ontological status of abrupt social transformations as a phenomenon of inauthenticity (Uneigentlishkeit) is emphasised due to the destruction of the middle principle, which is equally relevant for the ancient Eastern and modern Western (M. Heidegger) philosophical tradition. The fact of this community, between the subjects of which there is an extreme remoteness in time and space, allows us to speak about the ultimate universality of its meanings and, thus, the effectiveness of methodological application in a variety of humanitarian research practices: historiography, philosophy and psychology of history, sociology and literary studies.
Keywords: time of change; revolution; middle; balance; genuine – inauthentic